Influence of Peptide Conjugation Sites on Lunatin–Alumina Nanoparticles: Implications for Membrane Interaction and Antimicrobial Activity - Carolina Silva Ferreira; Lívia Mara Fontes Costa; Lúcio Otávio Nunes; Kelton Rodrigues de Souza; Giovanna Paula Araújo; Evgeniy S. Salnikov; Kelly Cristina Kato; Helen Rodrigues Martins; Adriano Monteiro de Castro Pimenta; Jarbas Magalhães Resende; Burkhard Bechinger; Rodrigo Moreira Verly (Pharmaceuticals)
Background/Objectives: The increasing prevalence of multidrug-resistant bacteria presents a major global health challenge, prompting a search for innovative antimicrobial strategies. This study aimed to develop and evaluate a novel nanobiostructure combining alumina nanoparticles (NPs) with the antimicrobial peptide lunatin-1 (Lun-1), forming peptide-functionalized nanofilaments. The main objective was to investigate how the site of peptide functionalization (C-terminal vs. N-terminal) affects membrane interactions and antibacterial activity. Methods: NP–peptide conjugates were synthesized via covalent bonding between lun-1 and alumina NP and characterized using transmission electron microscopy (TEM), X-ray diffraction (XRD), zeta potential analysis, dynamic light scattering (DLS), Fourier-transform infrared (FTIR), and solid-state 13C NMR. Antibacterial activities were assessed against different Gram-positive and Gram-negative strains. Biophysical analyses, including circular dichroism (CD), isothermal titration calorimetry (ITC), differential scanning calorimetry (DSC), and solid-state 2H NMR, were employed to evaluate peptide–membrane interactions in the presence of membrane-mimetic vesicles composed of POPC:POPG (3:1) and DMPC:DMPG (3:1). Results: Characterization confirmed the successful formation of NP–peptide nanofilaments. Functionalization at the N-terminal significantly influenced both antibacterial activity and peptide conformation compared to C-terminal attachment. Biophysical data demonstrated stronger membrane interaction and greater membrane disruption when lun-1 was conjugated at the N-terminal. Conclusions: The site of peptide conjugation plays a crucial role in modulating the biological and biophysical properties of NP–lunatin-1 conjugates. C-terminal attachment of lunatin-1 retains both membrane interaction and antibacterial efficacy, making it a promising strategy for the design of peptide-based nanotherapeutics targeting resistant pathogens.